The Method Of Determining The Probability Of Affection Of The Semiconductor Elements Under The Influence Of The Ultra-Short Duration Radio Pulses - Maksym Iasechko, Volodymyr Larin, Dmytro Maksiuta, Dmytro Karlov, Serhii Bazilo, Ivan Sharapa (International Journal of Advanced Science and Technology, 2020)
The studies to improve the affection accumulation method for the case of influence to the semiconductor element base by the multi-frequency space-time signals have been conducted. The estimates of the probability of affection of the semiconductor element under the influence of the multifrequency space-time signals have been obtained. As a result of the researches conducted, the method of affection accumulation for the case of the influence of MF STS on the semiconductor element base has been improved. This method involves the usage of statistical characteristics of thermal energy to estimate the probability of degradation of the p-n junctions for normal (diodes, transistors) and equable (integrated circuits) distribution laws. Keywords: semiconductor, affection, probability, microprocessor technology, control system, space-time signal, mathematical model.